2009
DOI: 10.1271/bbb.80646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Methylene-Interrupted Polyunsaturated Fatty Acid, Sciadonic (All-cis-5,11,14-eicosatrienoic Acid) on Lipid Metabolism in Rats

Abstract: We investigated effects of the non-methylene-interrupted polyunsaturated fatty acid, sciadonic acid (allcis-5,11,14-eicosatrienoic acid), on the lipid metabolism in rats, to identify the mechanism for the plasma and hepatic triacylglycerol-lowering effects of Japanese torreya (Torreya nucifera) seed oil. Sciadonic acid was isolated from torreya seed oil by the combination of urea-adduct with lipase-esterification. Sprague-Dawley (SD) male rats were fed with experimental diets containing 5% and 10% sciadonic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…1a). In addition, Scia can be elongated into 22:3Δ7,13,16 as previously showed in cultured cells 8,9 but in contrast with in vivo experiments 15,16,24 . In the present trial, this bishomo-sciadonic acid was identified by using DMOX derivatives and GC-MS.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…1a). In addition, Scia can be elongated into 22:3Δ7,13,16 as previously showed in cultured cells 8,9 but in contrast with in vivo experiments 15,16,24 . In the present trial, this bishomo-sciadonic acid was identified by using DMOX derivatives and GC-MS.…”
Section: Resultssupporting
confidence: 54%
“…These authors reported a large fall in the triglyceride concentration in the liver when rats consumed the Torreya oil but without investigating the effect on monoenes from hepatic triglycerides. Endo et al studied thereafter the nutritional effect of Scia purified from Torreya nucifera but the FA was supplied as the ethyl ester in the diet 16 . After a two-week trial, they observed a 50% reduction of the liver triglyceride concentration in rats previously fasted prior to the tissue collection.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the pool of monoenes in hepatocytes, SCD1 contributes to triacylglycerol neosynthesis, in which its availability regulates VLDL assembly and secretion. Its inhibition by Scia consequently reduced the secretion of triacylglycerols by hepatocytes, as previously underlined by in vivo studies . De novo neosynthesis of triacylglycerols is regulated by sterol regulatory element‐binding protein 1c, a hepatic gene transcription factor that stimulates the synthesis of lipogenic enzymes.…”
Section: Discussionmentioning
confidence: 72%
“…The physiological effects of Scia were consequently attributed to this arachidonate substitution. Nevertheless Scia was also shown to lower by itself the level of triacylglycerols in plasma and liver …”
Section: Discussionmentioning
confidence: 98%
“…Sciadonic acid 5(Z),11(Z),14(Z)-eicosatrienoic acid, SA), also known as podocarpic acid, is also an NMI PUFA present in lower levels in biota seed oil with similar biological properties to juniperonic acid. However, Endo et al suggested that SA may inhibit the synthesis of arachidonic acid from linoleic acid [32]. SA purification has been attempted via countercurrent chromatography and by open column adsorption chromatography followed by reverse-phase HPLC [6].…”
Section: Introductionmentioning
confidence: 99%